INTEGRATING ICT-COMPETENCES IN DESIGNING AND DEVELOPING LISTENING COURSE SYLLABI FOR ENGLISH LANGUAGE EDUCATION - Siahaan, Junita; Hamid, Syifa Fadhilah (TELL - US JOURNAL, 2024)
Incorporating ICT competencies into curricula, syllabuses, or course outlines is crucial to facilitate 21st century learning. However, as a receptive skill that the learner needs to develop, listening also requires supporting materials. such as ICTs, which can support instructors in providing the curriculum. Therefore, the purpose of this project is to create listening course syllabuses for the English Language Education Study Program (ELESP) that include ICT competencies. This research used Design and Development Research (DDR) as the methodology for their study. In this study, fourteen listening curricula from five Indonesian institutions served as the source of data. The following are the findings of this study: First, the ICT competencies are primarily incorporated, either explicitly or implicitly, in the following components: Learning Indicators (I), Learning Objectives (Lob), Teaching Method (TM), Materials (M), Assessment (AE), and Learning Media (LM). Furthermore, most integrated competencies in the current listening syllabuses are related to the utilization of audio and video files. Technology literacy, on the other hand, rises to the most applied level of ICT competencies, meaning that the ICT competencies included in the current listening curricula are still at the level of comprehension and use. Second, six methods for incorporating ICT Competencies into listening syllabuses were suggested by this study. Third, the study suggested creating integrated listening curricula for ICT competencies that encompass all ICT competency levels. Twelve components and a skill-based curriculum were used in the suggested curricula.